News of a book and a magazine from the library of Iturralde y Suit - Regueras Grande, Fernando (Huarte de San Juan. Geografía e Historia, 2016)
The author provides information of a French book of architecture and some issues of the Bulletin of the Real Academia de la Historia owned by himself with the bookplate of Juan Iturralde y Suit.
Keywords: Juan Iturralde y Suit; Navarre; History of Architecture; History of the Libraries; History of Art